Rapid gastric and intestinal transit is a major determinant of changes in blood glucose, intestinal hormones, glucose absorption and postprandial symptoms after gastric bypass - Nguyen, Nam Q.; Debreceni, Tamara L.; Bambrick, Jenna E.; Bellon, Max; Wishart, Judith; Standfield, Scott; Rayner, Chris K.; Horowitz, Michael (Obesity (Silver Spring, Md.), 2014)
Objective To evaluate the effect of modulating pouch emptying (PE) and SI transit of glucose after Roux‐en‐Y gastric bypass (RYGB) on blood glucose, incretin hormones, glucose absorption and gastrointestinal (GI) symptoms. Methods Ten RYGB patients were studied twice in random order, receiving either a 150 ml glucose drink (200 kcal) or the same solution infused into the proximal Roux‐limb at 4 kcal/min. Data were compared with 10 healthy volunteers who received a 4 kcal/min duodenal infusion. PE, cecal arrival time (CAT), blood glucose, plasma 3‐O‐methylglucose (3‐OMG), insulin, glucose‐dependent insulinotropic polypeptide (GIP), and glucagon‐like peptide‐1 (GLP‐1), and GI symptoms were measured. Results In RYGB subjects, the glucose drink emptied very rapidly (PE t50 = 3 ± 1 min) and intestinal glucose infusion was associated with higher blood glucose and plasma 3‐OMG, but lower plasma GLP‐1, GIP, insulin, and GI symptoms than oral glucose (all P < 0.001), and comparable to volunteers. In RYGB subjects, CAT correlated inversely with peak GLP‐1 (r = −0.73, P = 0.01), and plasma 3‐OMG correlated tightly blood glucose (r = 0.94, P < 0.0001). Conclusions After RYGB, reducing intestinal glucose delivery to 4 kcal/min is associated with higher blood glucose, greater glucose absorption, lower incretin responses, and less GI symptoms, supporting rapid transit contribution to the exaggerated incretin responses and “dumping symptoms”.